Injectable suture device for intraocular lens fixation. Issue 12 (December 2015) - Smith, Jesse M.; Erlanger, Michael; Olson, Jeffrey L.
Abstract : N/A: We describe a surgical technique for scleral fixation of a posterior chamber intraocular lens (PC IOL) using a 24‐gauge injectable polypropylene suture delivery system. A 3‐piece PC IOL is inserted into the anterior chamber of the eye. Two sclerotomies are made 1.5 mm posterior to the limbus using a microvitreoretinal blade. The 24‐gauge injector delivers a preformed suture loop into the eye with the double‐armed needles still external to the eye. Each polypropylene IOL haptic is directed through the loop using microforceps. The suture loop is tightened around the haptic, and the attached needles are used to fixate the IOL to the sclera and close the sclerotomies simultaneously. This technique has been used in an ex vivo porcine eye and in an aphakic patient. In the latter, the IOL was quickly fixated to the sclera and maintained a stable position postoperatively. Financial Disclosure : Dr. Olson has a patent pending for the device described in this article. No other author has a financial or proprietary interest in any material or method mentioned.